Ensino de mando por informação com interrupção de cadeia em indivíduos com TEA vocais ou que utilizam comunicação suplementar e/ou alternativa: uma revisão sistemática - Tognozzi, Julia dos Reis (2022)
One of the main characteristics of people diagnosed with ASD is the deficit in communication. Teaching verbal operants has become fundamental for this population, among them, the mand. The present study aims to carry out a systematic review and analyze the 18 selected studies about mand for information, which use behavioral chain interruption strategies with individuals with ASD and compare the effectiveness of the results obtained between individuals who communicate through vocal means with the obtained by individuals who communicate through augmentative and/or alternative communication (AAC). The comparison between the two media of children with ASD was not explored in previous reviews. This review followed the PRISMA guidelines and was performed by searching the PsycInfo, Education Resources Information Center (ERIC), MEDLINE and Wiley Online Library databases. The results indicated that, in all the studies found, participants learned to mand for information in the behavioral chains taught, participants who communicated through vocal means and through AAC. Due to the limited number of studies with participants who communicate through AAC, it was not possible to make a satisfactory analysis of the performance of these participants relating to vocal participants. In most studies, participants communicated through vocal means. Participants who communicated through AAC showed failures in generalization, requiring changes in teaching procedures for generalization to be achieved. The same occurred with some vocal participants who had a less developed verbal repertoire (less than 100 tacts, inconsistency in mands by items and 20 or less intraverbals and intraverbals with only one type of question)